Simultaneous Determination of Orelabrutinib, Zanubrutinib, Ibrutinib and Its Active Metabolite in Human Plasma Using LC-MS/MS - Sun, Lu-Ning; Zhao, Yang; Qian, Zhou-Yi; Chen, Xiang-Long; Ma, Hong; Guo, Yu-Jiao; Shen, Hao; Wang, Yong-Qing (Molecules (Basel, Switzerland), 2023)
Ibrutinib, orelabrutinib, and zanubrutinib are all Bruton’s tyrosine kinase inhibitors, which have greatly improved the treatment of B-cell malignancies. In this study, an LC-MS/MS method was developed and validated for the determination of orelabrutinib, zanubrutinib, ibrutinib, and its active metabolite dihydrodiol ibrutinib in human plasma. The Ibrutinib-d5 was used as the internal standard. Pretreatment was performed using a simple protein precipitation step using acetonitrile. The ACQUITY UPLC HSS T3 column (2.1×50 mm, 1.8 μm) was used to separate the analytes, and the run time was 6.5 min. The mobile phase consisted of acetonitrile and 10 mM of ammonium formate, which contained 0.1% formic acid. The multiple reactions’ monitoring transitions were selected at m/z 428.1→411.2, 472.2→455.2, 441.1→304.2, 475.2→304.2 and 446.2→309.2 respectively for orelabrutinib, zanubrutinib, ibrutinib, dihydrodiol ibrutinib and ibrutinib-d5 using positive ion electrospray ionization. The standard curves were linear, from 0.400 to 200 ng/mL for ibrutinib and dihydrodiol ibrutinib, 1.00–500 ng/mL for orelabrutinib, and 2.00–1000 ng/mL for zanubrutinib. Selectivity, the lower limit of quantitation, precision, accuracy, matrix effect, recovery, stability, and dilution integrity all met the acceptance criteria of FDA guidance. This method was used to quantify the plasma levels of orelabrutinib, zanubrutinib, ibrutinib, and dihydrodiol ibrutinib in clinical patients.